Simulating plant produced material in the laboratory to replicate rheological and fatigue properties - Oshone, Mirkat; Pires, Gustavo Menegusso; Jiménez del Barco Carrión, Ana; Rahbar-Rastegar, Reyhaneh; Airey, Gordon; Daniel, Jo Sias; Bailey, Helen; Smith, David (Taylor & Francis, 2018)
As part of an effort by agencies and industry to move towards performance-based design to evaluate mixtures in the laboratory at a smaller scale before moving to full scale operation, laboratory protocols exist to simulate the aging that occurs as a material is produced. However, recent research has shown that these existing protocols may not accurately represent the changes a material experiences in a plant. Moreover, due to the focus of previous studies on the ability of the current method to replicate mixture characteristics and performance in an undamaged state, there is a lack of information as it relates to the damaged state. This paper presents a concise description of a study undertaken on a particular mixture to evaluate the differences in the behaviour of a standard asphalt concrete mixture produced in the laboratory and in the plant to assess the anticipated field performance at the mixture design stage. The results, in terms of the rheological properties of binders extracted and recovered from laboratory and plant produced mixtures as well as rheological, repeated cyclic fatigue, and cracking performance evaluation of the asphalt mixtures, have shown the ability of a short-term oven aging protocol to replicate plant produced material in the laboratory.